Ergative marking in Nyagrong-Minyag (Xinlong, Sichuan) - Suzuki, Hiroyuki (2024)
This paper describes the usage of the ergative case in Nyagrong-Minyag, one of the rGyalrongic languages spoken in Xinlong County, Ganzi Prefecture, Sichuan. The ergative marker in this language functions as an emphatic only for the agent of the transitive verb, but has a limited use that can be classified into two aspects: 1) ergativity is not allowed for first and second person arguments; 2) an ergative marker may be optionally used on third person agents for pragmatic effects.